EFFECT OF INQUIRY LEARNING MODEL AND MOTIVATION ON PHYSICS OUTCOMES LEARNING STUDENTS - Dahlia Megawati Pardede; Sondang Rina Manurung (Jurnal Pendidikan Fisika, 2016)
The purposes of the research are: (a) to determine differences in learning outcomes of students with Inquiry Training models and conventional models, (b) to determine differences in physics learning outcomes of students who have high motivation and low motivation, (c) to determine the interaction between learning models with the level of motivation in improving student Physics learning outcomes. The results were found: (a) there are differences in physical students learning outcomes are taught by Inquiry Training models and conventional models. (b) learning outcomes of students who are taught by Inquiry Learning Model Training better than student learning outcomes are taught with conventional model. (c) there is a difference in student's learning outcomes that have high motivation and low motivation. (d) Student learning outcomes that have a high motivation better than student learning outcomes than have a low motivation. (e) there is interaction between learning and motivation to student learning outcomes. Learning outcomes of students who are taught by the model is influenced also by the motivation, while learning outcomes of students who are taught with conventional models are not affected by motivation.